Desain Sport Center Desa Gayaman Kabupaten Mojokerto - Rendis Eka Arisandi; M. Adik Rudiyanto (BADAN PENERBIT STIEPARI PRESS, 2025)
The availability of adequate sports facilities at the village level is an important factor in supporting the improvement of health, quality of life, and social interaction of the community. Gayaman Village, located in Mojokerto Regency, has great potential for the development of public facilities that support a healthy lifestyle. However, until now there has been no integrated sports facility that can accommodate various physical and social activities of residents. This study aims to design a functional, contextual, and sustainable Sport Center in response to the needs of the Gayaman Village community. The methods used include field observation, interviews with residents and village officials, site analysis, and architectural design based on tropical architectural principles. The design results show that this Sport Center includes indoor and outdoor sports zones, multipurpose rooms, and other supporting facilities that are designed to be inclusive and environmentally friendly. It is hoped that this design can be a reference in the development of village sports facilities that are adaptive to local conditions and community needs.